2014
DOI: 10.1007/s11033-014-3652-1
|View full text |Cite
|
Sign up to set email alerts
|

The association between C-159T polymorphism in CD14 gene and susceptibility to tuberculosis: a meta-analysis

Abstract: The association between CD14 gene C-159T polymorphism and tuberculosis (TB) susceptibility remains inconclusive. To derive a more precise estimation of the correlation, we performed a meta-analysis summarize the possible at a systematic manner. PubMed, HighWire and ScienceDirect databases covering all papers (up to November 2012) were searched. Statistical analyses were conducted by Rev-Man and STATA. Random- and fixed-effect models were used to estimate pooled odds ratios (ORs) and 95% confidence intervals (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
4
0
1
Order By: Relevance
“…In contrast, no associa-tion was found between CD14 polymorphism and different forms of TB disease in white and Mestizos ethnic groups from Colombia (Pacheco et al, 2004). A metaanalysis by Yuan et al suggested that C-159T polymorphism in CD14 gene was associated with an increased risk of TB, especially in Asians, but not in Caucasians (Yuan et al, 2014). The explanation for these differences has not been found.…”
Section: Cd14 Moleculementioning
confidence: 97%
“…In contrast, no associa-tion was found between CD14 polymorphism and different forms of TB disease in white and Mestizos ethnic groups from Colombia (Pacheco et al, 2004). A metaanalysis by Yuan et al suggested that C-159T polymorphism in CD14 gene was associated with an increased risk of TB, especially in Asians, but not in Caucasians (Yuan et al, 2014). The explanation for these differences has not been found.…”
Section: Cd14 Moleculementioning
confidence: 97%
“…Listed in the white portion of the Venn diagram are non-HLA genes with alleles that associate with Candida disease susceptibility 150,151,153,284–298 . Likewise, listed in the black portion are non-HLA genes with alleles that associate with Mycobacteria disease susceptibility 160162,299315 . Listed in the gray overlap are nine genes with alleles that associate with both Candida and Mycobacteria disease susceptibility: IRF8 154 , MBL2 156,316,317 , TLR2 157,314,318 , IL10 319321 , IL12B 110,320 , IL12RB1 322325 , RLTPR 326 , RORC 327 and STAT1 206,207,328332 .…”
Section: Figurementioning
confidence: 99%
“…As shown from our result, there is significant SNP diversity at the promoter region of CD14 gene, indicating selection sweep between the disease tolerant N'Dama and susceptible White Fulani cattle. Other reports have shown significant association of CD14 gene polymorphism with varying disease phenotypes, including monocyte surface expression in Canadian Holstein and Jersey cows during bovine mastitis [13], and in Chinese Holstein cows during bovine tuberculosis [15,38,46,47].…”
Section: Discussionmentioning
confidence: 96%